2017
DOI: 10.1097/yct.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Electroconvulsive Therapy and Associated Cognitive Change in Schizophrenia

Abstract: Our present findings suggest that an acute course of ECT is effective in schizophrenia and may have cognitive benefits for some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
4
11
2
Order By: Relevance
“…reported no significant difference with the Mini‐Mental State Examination. Our results, however, are similar to our recent ECT study, which also found improvement in cognitive outcomes. This improvement in cognitive outcomes can be explained by the possible difference in the method of ECT administration: Kaster et al .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…reported no significant difference with the Mini‐Mental State Examination. Our results, however, are similar to our recent ECT study, which also found improvement in cognitive outcomes. This improvement in cognitive outcomes can be explained by the possible difference in the method of ECT administration: Kaster et al .…”
Section: Discussionsupporting
confidence: 91%
“…Evidence regarding the effectiveness and cognitive side‐effects of different types of ECT in schizophrenia is scarce. Although a recent Singapore‐based study comparing bifrontal, bitemporal, and right unilateral ECT showed no difference in effectiveness and cognitive outcomes, it was a retrospective study with small sample sizes and significant limitations in methodology. Phutane et al .…”
Section: Methodsmentioning
confidence: 99%
“…The authors note that the differences reported were small and perhaps clinically insignificant. In the aforementioned Tor et al [30], the efficacy of 3 different placements was compared. No single placement showed significant superiority.…”
Section: Resultsmentioning
confidence: 99%
“…[30] compared the symptomatic and cognitive outcomes of patients with schizophrenia receiving one of 4 ECT modalities: bitemporal ECT with age-based dosing, right unilateral (RUL) ECT with seizure threshold (ST)-based dosing, bitemporal ECT with ST-based dosing, or bifrontal ECT with ST-based dosing. The Montreal Cognitive Assessment and BPRS were administered to 62 patients before and after a course of ECT.…”
Section: Resultsmentioning
confidence: 99%
“…5,[14][15][16][17][18] A further 17 studies included at least one patient older than 60 years of age within a mixed-age cohort, or a mixed-diagnoses cohort where outcomes specific to patients with primary psychotic conditions were reported (Table 2). 4,10,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]…”
Section: Resultsmentioning
confidence: 99%